Break Down the Silos: A Conceptual Framework on Multisectoral Approaches to the Prevention and Control of Vector-Borne Diseases. (29th October 2020) - Zhong, Qingxia; Fouque, Florence
Abstract: The need for multisectoral approaches (MSAs) in prevention and control of vector-borne diseases (VBDs) has been identified. VBD programs often involve collaborations between health and nonhealth sectors; however, a systematic framework describing the process, requirements, challenges, and benefits of MSAs has been missing. A recent guidance document from UNICEF/UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases provides a framework to implement MSAs for prevention and control of VBDs. This article gives an introduction to the guidance document and describes the conceptual framework and coordination process. The next steps will be to test the framework through implementation research in specific VBD cases studies. The guidance document will thus be refined based on iterative and comprehensive monitoring and evaluation systems to assess the performance and impact of MSAs. The advocacy for MSA and necessary capacity building will be integrated into the testing of the framework.